The Relationship of Components of Mindfulness with Cognitive Emotion Regulation Strategies: The Mediating Role of Alexithymia - Seyed Mohammad Hossein Mousavi Nasab; Masoumeh S Sajjadi (Journal of Kerman University of Medical Sciences, 2017)
Introduction: The aim of this study was to investigate the causal relationship of mindfulness and cognitive emotion regulation strategies and mediating role of alexithymia in this relationship. Method: In this descriptive-correlational study, 355 students (192 femalesand 163 males) were recruited from ShahidBahonar university of Kerman through randomclustered sampling method. Five- facet mindfulness questionnaire (FFMQ), Toronto alexithymia scale (TAS) and cognitive emotion regulation strategies questionnaire (CERQ) were used as instruments. Data were analyzed through SPSS22 and Mplus5 software packages and using path analysis and mediation analysis. Results: There was significant relationship between facets of mindfulness, alexithymia and cognitive emotion regulation strategies. In addition, facet of difficulty in identifying feelings had partial mediating role in relationship between facets of mindfulness and positive emotion regulation strategies. Conclusion: Results indicated that mindfulness has a significant role in prediction of different aspects of alexithymia and cognitive emotion regulation and it can be useful for improvement of emotional problems.